Faktor Determinasi Income Smoothing dengan Tarif Pajak Efektif sebagai Variabel Mediasi - Haryadi, Teddy; Septiana, Gina; Rikayana, Hadli Lidya (SAFE-Network, 2023)
Income Smoothing (IS) is one of the earnings management carried out by the company to demonstrate management's ability to generate profits for external parties. The purpose of this study was to determine the effect of Return on Equity (ROE), Debt to Total Assets (DTA), and Current Ratio (CR) on IS with the effective tax rate as a mediating variable. The effective tax rate is expected to influence the relationship between ROE, DTA, and CR on IC. The amount of tax paid by the company is directly proportional to the increase in company profits. The object of research is all companies engaged in the mining sector that are on the Indonesia Stock Exchange (IDX) in the analysis period for the 2019 to 2022 financial reporting years. The number of companies that meet the criteria is 20 companies. The data analysis technique uses the Partial Least Square (PLS) method with the WarpPLS 8.0 application. Based on the results of the analysis, DTA, CR and effective tax rates have a positive effect on IS. ROE has no effect on IS. ROE and CR have a negative effect on the effective tax rate. DTA has no effect on the effective tax rate. This study also shows that effective tax rates can mediate the relationship between CR and IS, so that taxes and effective tax rates cannot mediate the relationship between DTA and ROE with IS. This study also found that ROE, DTA, CR, and effective tax rates can affect IS by 6%.